THE EFFECT OF E-TRUST AND E-SERVICE QUALITY IN ONLINE REPURCHASE INTEREST OF TIX ID (Survey on TIX ID Application User in Bandar Lampung) - Wicaksono, Rendra Wiku; hartono, Hartono; Subagja, Ghia (Jurnal Kompetitif Bisnis, 2021)
This study was aimed to find out the effect of e-trust and e-service quality in online repurchase interest of TIX ID application users in Bandar Lampung. This type of explanatory research with a quantitative approach. The population in study were users of the TIX ID application user in Bandar Lampung. The data was obtained from a questionnaire. the sampling technique used purposive sampling with a total sample of 100 respondents. Data analysis in this study used multiple linear regression analysis with SPSS 25.0 computer software. Based on the results of research and data analysis shows that of e-trust and e-service quality in online repurchase interest 51,5%. While the partial test results of each variable showed that e-trust significantly affected in online repurchase interest 38,1%, and e-service quality significantly affected in online repurchase interest 30,8%.